2021
DOI: 10.1111/are.15621
|View full text |Cite
|
Sign up to set email alerts
|

Bovine lactoferrin in fish culture: Current research and future directions

Abstract: Lactoferrin is a mammalian cationic iron‐binding glycoprotein of the innate immune system that belongs to the transferrin family of proteins. Present in colostrum, milk and tears, and exhibiting a wide range of biological properties in vitro and in vivo, lactoferrin is a nutraceutical component used as a food supplement for humans. Evidence from veterinary medicine and animal production suggests the potential use of lactoferrin as a microbicide, microbiostatic, microbiota modulator or immunostimulant. Bovine l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…An effective strategy to counteract fish intestinal inflammation is the dietary use of functional substances that exert metabolic regulation, antioxidant properties, and immune promotion [ 4 , 9 , 10 , 11 , 12 ]. Lactoferrin (LF), a glycoprotein with a molecular weight of 78–80 kDa, is rich in milk [ 13 , 14 ] and has many biological functions [ 14 , 15 , 16 ]. A previous study showed that dietary LF supplementation could enhance the growth performance of early-weaned piglets by promoting the proliferation of intestinal beneficial bacteria, such as lactic acid bacteria; inhibiting the proliferation of E .…”
Section: Introductionmentioning
confidence: 99%
“…An effective strategy to counteract fish intestinal inflammation is the dietary use of functional substances that exert metabolic regulation, antioxidant properties, and immune promotion [ 4 , 9 , 10 , 11 , 12 ]. Lactoferrin (LF), a glycoprotein with a molecular weight of 78–80 kDa, is rich in milk [ 13 , 14 ] and has many biological functions [ 14 , 15 , 16 ]. A previous study showed that dietary LF supplementation could enhance the growth performance of early-weaned piglets by promoting the proliferation of intestinal beneficial bacteria, such as lactic acid bacteria; inhibiting the proliferation of E .…”
Section: Introductionmentioning
confidence: 99%